Yeasts in food : Beneficial and detrimental aspects - Boekhout, T. (Woodhead Publishing in food science, technology, and nutrition ;, 2003)
Yeasts play a crucial role in the sensory quality of a wide range of foods. This book provides a comprehensive review of the methods for their detection, identification and analysis as well as the role of yeasts in several food products including dairy products, meat, fruit, bread and beverages.